Indonesia Interest toward G20 Pandemic Fund: Global Health Diplomacy Perspective - Ahmada, Saqib Fardan (Universitas Airlangga, 2024)
In the last three years, during the COVID-19 pandemic shocks, the discussion for economic recovery and global health development agenda prevailed. To date, the discussion has shifted from recovery to more extensive moves such as strengthen the current global health architecture. Specifically, prepare for the next pandemic and reduce potential risks. Countries around the world are interested in this topic and the Group of Twenty (G20), the premier economic forum summit, also focuses on this issue. This kind of